Development of Aspergillus oryzae BCC7051 as a Robust Cell Factory Towards the Transcriptional Regulation of Protease-Encoding Genes for Industrial Applications - Sarocha Panchanawaporn; Chanikul Chutrakul; Sukanya Jeennor; Jutamas Anantayanon; Kobkul Laoteng (Journal of Fungi)
Enzyme-mediated protein degradation is a major concern in industrial fungal strain improvement, making low-proteolytic strains preferable for enhanced protein production. Here, we improved food-grade Aspergillus oryzae BCC7051 by manipulating the transcriptional regulation of protease-encoding genes. Genome mining of the transcription factor AoprtR and computational analysis confirmed its deduced amino acid sequence sharing evolutionary conservation across Aspergillus and Penicillium spp. The AoPrtR protein, which is classified into the Zn(II)2-Cys6-type transcription factor family, manipulates both intra- and extracellular proteolytic enzymes. Our transcriptional analysis indicated that the regulation of several protease-encoding genes was AoPrtR-dependent, with AoPrtR acting as a potent activator for extracellular acid-protease-encoding genes and a likely repressor for intracellular non-acid-protease-encoding genes. An indirect regulatory mechanism independent of PrtR may enhance proteolysis. Moreover, AoPrtR disruption increased extracellular esterase production by 2.55-fold, emphasizing its role in protein secretion. Our findings highlight the complexity of AoPrtR-mediated regulation by A. oryzae. Manipulation of regulatory processes through AoPrtR prevents secreted protein degradation and enhances the quantity of extracellular proteins, suggesting the low-proteolytic variant as a promising platform for the production of these proteins. This modified strain has biotechnological potential for further refinement and sustainable production of bio-based products in the food, feed, and nutraceutical industries.